Comparison of periodontal inflammatory parameters among habitual gutka-chewers and naswar-dippers: a split-mouth retrospective clinical study. (17th February 2018) - Akram, Zohaib; Abduljabbar, Tariq; Hosain, Mervyn; Al-Sowygh, Zeyad H.; Al-Hamoudi, Nawwaf; Vohra, Fahim; Javed, Fawad
Abstract: Objective: The aim of the present split-mouth retrospective study was to compare the clinical periodontal parameters among gutka- chewers and naswar -dippers. Methods: A structured questionnaire was used to record demographic information. Jaw quadrant in which, gutka or naswar were placed were defined as "test-sites". The remaining jaw quadrants were designated as "control-sites". Clinical [plaque index (PI), bleeding on probing (BOP), probing pocket depth (PPD) and clinical attachment loss (CAL)] and radiographic [alveolar bone loss (ABL)] parameters were compared among gutka -chewers and naswar -dippers in the test- and control sites. Data were analysed using non-parametric Wilcoxon signed rank test followed by post hoc analyses with the Bonferroni correction. p  < .05 were considered statistically significant. Results: Seventy-five gutka -chewers and 72 naswar -dippers with mean ages of 45.2 ± 0.8 years and 47.3 ± 2.8 years, respectively were included. Gutka -chewers and naswar-dippers were consuming their respective smokeless tobacco product 10.2 times and 8.5 times daily for 15.1 ± 2.7 and 12.3 ± 3.4 years, respectively. Among gutka -chewers and naswar -dippers, scores of PI, BOP, PPD ≥4 mm, CAL and ABL were significantly higher in the test-sites compared with their respective control-sites ( p  < .01). Conclusions: Periodontal inflammatory parameters were poorer in the test-sites among g utka -chewers and naswar -dippers compared with the control-sites.